Family engagement strategies in palliative care: overcoming challenges - Souza, Amanda Gomes de (2024)
Objective: To investigate the main difficulties faced by family members in the process of engaging in palliative care and to identify effective strategies for preventing and alleviating suffering. Method: This is an integrative review, using the Scientific Electronic Library Online (SCIELO) and the Latin American and Caribbean Health Sciences Literature (LILACS) databases, with the descriptors integrative palliative care, palliative nursing at the end of life, and palliative care. The inclusion criteria were full-text articles available in Portuguese, published in the last five years. Results: The main difficulties identified were lack of knowledge, difficulty in acceptance, and psychosocial perspective. The strategies mentioned were symptom control, psychosocial, and spiritual intervention. Conclusion: This study highlights the complexities of family involvement in palliative care and suggests the need for future research to develop more integrated and effective approaches to address the identified challenges.